AN ANALYSIS OF STUDENTS’ INTERNAL AND EXTERNAL PROBLEMS IN SPEAKING ENGLISH: A CASE STUDY AT AN ISLAMIC BOARDING SCHOOL - Iqbal Rosyid (English Didactic, 2020)
There were causes of students' problems in speaking English such as vocabulary, grammar and pronunciation problems. The current research tries to analyze the students’ internal and external problems in speaking English in class and beyond the classroom context at a private Islamic Boarding School as well as the strategies that the students have to face those problems. This study is conducted qualitatively using a case study approach. The participants are grade 9th of a junior high school students. The data analysis was carried out using Miles, Huberman, and Saldana (2018, p.74) that consists of data reduction, data display and conclusion drawing and verification. The findings show that students have cognitive and psychological internal problems while they learn English speaking. The cognitive-related internal problems are English grammatical mastery, pronunciation issues, as well as vocabulary limitation. The psychologically-related internal problems that occur are fear of making mistakes, shyness, anxiety, lack of confidence, and lack of motivation. The findings regarding English speaking external problems do not come only from classroom management-related issues but also school language policy. Students revealed that they mostly use memorization and cognitive strategy for direct learning strategies and socialization for indirect learning strategy.